2019
DOI: 10.2147/tacg.s198992
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>ACE</em> gene polymorphism and its association with serum erythropoietin and hemoglobin ‎in Iraqi hemodialysis patients</p>

Abstract: Purpose To evaluate the frequencies of angiotensin-converting enzyme gene ‎polymorphism in ‎Iraqi hemodialysis patients and to examine the association ‎between this polymorphism and ‎serum erythropoietin and hemoglobin levels.‎ Methods In this study, 70 chronic renal failure Iraqi patients on ‎maintenance ‎hemodialysis (patient group) and 20 healthy subjects (control ‎group) were genotyped for ‎ angiotensin-converting enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Rahimi et al [8], in Iran discovered that the frequencies of ACE genotypes and allles were not statistically different compared to ESRD patients and controls; the latest findings are inconsistent with the current study showing that there is a significant statistical difference between patients and the control group in SNP ACE genotypes (DD and II). The current study did not match the results of another local study in Baghdad by Al-Radeef et al [9] showed that most frequent ID genotype followed by DD and II in overall CKD events, with no significant difference between chronic kidney disease and healthy subjects in these genotypes [9] . This mismatch can be due to a very important reason related by the small size of the studied samples, environmental heterogeneity and natural genetic in different ethnic groups or it might as the result of the method that is used in this study.…”
Section: Evaluate the Concentration And Purity Of Extracted Dnacontrasting
confidence: 99%
See 2 more Smart Citations
“…Rahimi et al [8], in Iran discovered that the frequencies of ACE genotypes and allles were not statistically different compared to ESRD patients and controls; the latest findings are inconsistent with the current study showing that there is a significant statistical difference between patients and the control group in SNP ACE genotypes (DD and II). The current study did not match the results of another local study in Baghdad by Al-Radeef et al [9] showed that most frequent ID genotype followed by DD and II in overall CKD events, with no significant difference between chronic kidney disease and healthy subjects in these genotypes [9] . This mismatch can be due to a very important reason related by the small size of the studied samples, environmental heterogeneity and natural genetic in different ethnic groups or it might as the result of the method that is used in this study.…”
Section: Evaluate the Concentration And Purity Of Extracted Dnacontrasting
confidence: 99%
“…According to the Promega protocol of the manufacturer, genomic DNA extracted from blood samples using the RediaperTM Blood gDNA Miniprep System (Promega, USA) provides a quick, simple technique for mammalian blood preparation of purified and intact DNA, the quality and concentration of extracted DNA were analyzed by using Nano drop spectrophotometer 1000 -Taiwan that assessed the consecration at (ng/ul) and evaluated the quality (purity) of DNA by reading the absorbance at (260/280 nm) and the DNA bands have been seen by electrophoresis of the agarose gel. The polymorphism of the ACE gene was detected using polymerase chain reaction (PCR) using the technique defined by Al-Radeef et al [9]. The SNP in ACE gene involves two allelic forms (D and I ), corresponding to the deletion or the insertion that forms three probable genotypes: DD, II or ID.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACE rs4646994 D/D genotype was associated with a poor response to rHuEpo in HD Korean patients, suggesting that it could be a useful genetic tool in predicting Epo requirement and responsiveness in HD patients. 10 Kiss et al, 27 working on Hungarian and Al-Radeef et al, 28 working on Iraqi HD patients, reported that ACE polymorphism had a non-significant effect on the Hb level. These variations may arise from the exact SNPs tested; we explored the ACE G2350A (rs4343) effect while they examined rs1799752 and rs4646994, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This notion contradicts the finding of Al-Radeef et al, who showed that another rs1799752 I/D and D/D genotypes had a higher serum Epo level compared to the I/I genotype. 28 …”
Section: Discussionmentioning
confidence: 99%